Cyanidin-3-O-glucoside mediated photodegradation of profenofos in water. (December 2022) - Lv, Pei; Tao, Yumeng; Zhang, Nan; Yang, Yawei; Wu, Xiangwei; Li, Qing X.; Hua, Rimao
Abstract: Flavonoids can sensitize and quench the photolysis of pesticides such as profenofos in surface water. Profenofos has been frequently detected in surface and underground water. The present study investigated the photolysis of profenofos under various conditions, including natural and artificial light illumination, with and without cyanidin-3- O -glucoside (Cy3G) and in pure and surface water. The degradation half-lives of profenofos in distilled water with 10 equivalents Cy3G of profenofos were 21.7 min, 9.5 h, 12.5 h and 180 h under high-pressure mercury light, UV, Xenon lamp and solar irradiation, respectively, while those without Cy3G were 8.1 min, 6.1 h, 8.2 h and 89.9 h, respectively. The photolysis rate of profenofos under sunlight and artificial light was reduced by 1.5–2.7 times due to Cy3G, compared to the Cy3G-free control. Under sunlight irradiation, the effects of Cy3G on profenofos photolysis were larger than those under high-pressure mercury lamp irradiation. Cy3G also significantly reduced the photolysis rate of profenofos under different pH conditions and in natural water. In addition, Cy3G exhibited a significant capacity of scavenging hydroxyl radicals and quenching 1 O2 in water. The effect of Cy3G on profenofos photolysis was demonstrated through their interrelations in the natural environment. These findings can help understanding of the effect of flavonoids on profenofos photolysis and are of significance for predicting the degradation kinetics of profenofos and accurately assessing its potential biological impacts. Graphical abstract: Image 1 Highlights: Cyanidin-3- O -glucoside (Cy3G) decreased photolysis rate of profenofos. Profenofos preferred photodegradation in high pH value with/or without Cy3G. The photolysis rates of profenofos were lower in natural water than in distilled water. Cy3G exhibited the capacity of scavenging hydroxyl radicals and 1 O2 in water.